MENDAMAIKAN AGAMA DAN SAINS: (Telaah Pemikiran Teori Quantum Nidhal Guessoum) - Ahmad Zainor Rozikin; Ahidul Asror; Subakri Subakri (Instructional Development Journal, 2024)
The debate regarding religion and science is something that is interesting to continue to study. The conflict between religion and science is getting hotter when scientists consider themselves rational with the hope that they will uncover the fundamental laws that govern behavior, matter and style. On the other hand, religionists with views that are irrational and obedient to religious dogmas claim to contain truths that cannot be changed and modified. Interestingly, there are Muslim scientists who try to respond to the development of modern science from a different point of view, namely Nidhal Guessoum. The presence of Nidhal Guessoum in the discourse arena to integrate religion and science has enriched thinking in the Islamic world. This study aims to determine the construction of religion and science as well as the relationship between religion and science in Nidhal Guessoum's quantum theory. Using a qualitative research method, the literature examines the contents of the book, the substance of the discussion, and the focus of the studies and thoughts of the figures. The objects are books and research journals that contain Nidhal Guessoum's thoughts on religion and science. And finally the findings in this study that Nidhal guessoum specifically constructs how Islam views scientific theories including: Islam and Cosmology, Islam and Design Arguments, Islam and Anthropic Principles, Islam and Evolution in addition to constructing religion and science Nidhal Guessoum also offers theories quantum which is based on three principles, namely the principle of not contradicting, layered interpretation, and theistic falsification.